THE IMPACT OF SMALL INTESTINAL BACTERIAL OVERGROWTH ON THE GROWTH OF CHILDREN AND ADOLESCENTS - Alexandre Neves da Rocha Santos; Ana Cristina Fontenele Soares; Ricardo Palmero Oliveira; Mauro Batista de Morais (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate the association between small intestinal bacterial overgrowth (SIBO) and weight and height impairment in children and adolescents with gastroenterology diseases. Methods: Observational and retrospective study. All 162 patients aged less than 19 years old who underwent breath test in search of SIBO between 2011 and 2016 were studied. Breath test was collected after the intake of 10 grams of lactulose. The concentration of hydrogen and methane was measured for 180 minutes after the beginning of the test by 12i QuinTronMicroLyzer device. Results: SIBO was identified in 51 (31.5%) patients. There was no difference between the age of those with (mean=8.7y.o; 25th and 75th percentile: 4.6 and 11.3) and without (mean=7.9y.o 25th and 75th percentile: 4.8 and 12.2) SIBO (p=0.910). There was no association between gender and SIBO (male 26.3% vs. female 36.3%, p=1.00). A lower median of height-for-age Z score (mean=-1.32; 25th and 75th percentile: -2.12 and -0.08 vs. mean=-0.59; 25th and 75th percentile: -1.57 and 0.22; p=0.04) was demonstrated in children with SIBO when compared with children without it. There was no difference between the BMI-for-age Z score of patients with (mean=-0.48) and without SIBO (mean=-0.06) (p=0.106). The BMI of patients with SIBO (median=15.39) was lower than of those without it (median=16.06); however, the statistical analysis was not significant (p=0.052). The weight-for-age Z score was lower in patients with SIBO (mean=-0.96) than in those without SIBO (mean=-0.22) (p=0.02) Conclusions: Children and adolescents with SBIO associated with diseases of the gastrointestinal tract have lower weight and height values.